Ge-gen decoction alleviates primary dysmenorrhoea symptoms in a rat model - Yazhen Xie; Haifeng Xu; Zhijuan Gu (Journal of Obstetrics and Gynaecology, 2024)
Background Existing treatments for primary dysmenorrhoea (PD), such as NSAIDs, impart side effects. Ge-Gen decoction (GGD), a traditional Chinese medicine, has shown promise in treating PD, but its exact mechanisms remain unclear. Here, we aimed to investigate the efficiency of GGD in alleviating PD using a rat model to understand its precise mechanism of action.Methods We established a rat model of dysmenorrhoea induced by oestradiol and oxytocin. The PD rats were administered GGD or Ibuprofen (positive control) intragastrically once daily for seven consecutive days. Serum levels of prostaglandin E2 (PGE2), prostaglandin F2 alpha (PGF2α), β-endorphin (β-EP), thromboxane B2 (TXB2), 6-keto-prostaglandin F1α (6-keto-PGF1α) were determined using an enzyme-linked immunosorbent assay (ELISA). The expression levels of oestrogen receptor alpha (ERα) and cyclooxygenase-2 (COX-2) in uterine tissue were measured using immunohistochemical assays, and those of phosphorylated and total extracellular signal-regulated protein kinases 1 and 2 (ERK1/2) were assessed using western blot analysis.Results Treatment with GGD significantly reduced writhing behaviour, histopathological scores, and levels of COX-2, PGE2, and PGF2α in the serum of PD rats. Additionally, GGD increased β-EP content and inhibited ERK1/2 activation and ERα expression in uterine tissues.Conclusions The results of this study suggest that GGD alleviates PD in rats by suppressing the COX-2-mediated release of PGE2 and PGF2α, modulating the ERα/ERK1/2/COX-2 pathway, and increasing β-EP content. These results provide insights into the potential mechanisms of GGD in treating PD and support its further investigation as an alternative therapy for this condition.